Influence of Banking Image, Financing Procedure and Sharia Principles to Customer Decision in Taking Financing PT. Bank Muamalat Indonesia Tbk Branch Makassar - Verawaty, Verawaty (Patria Artha Journal of Accounting dan Financial Reporting, 2018)
The purpose of this study is to know the image banking, financing procedures and principles ofsharia partially and simultaneously to the decision of the customer ini taking financing at PT.Bank Muamala Indonesia branch of Makassar. The analytical method use is multiple linear regression analysis. The population of this study isall customers who take the financing. To see the independent variable to depent variableis donepartially or simultaneously with level of trust 95%.Partially indicate that banking image, financing procedure and also syariah principles havepositif but not significant influence to customer decision in taking financing. Simultaneouslyshow the three variable have positive and significant effect. This result implies that the bank isable to create added value in the management of human resources, so that in the end canincrease the distribution of corporate financing.